HYPORHEIC EXCHANGE OF REACTIVE AND CONSERVATIVE SOLUTES IN STREAMS-TRACER METHODOLOGY AND MODEL INTERPRETATION - Jonsson K.; Johansson H.; Worman A. (My University, 2003)
A transient storage model is evaluated using results from a tracer experiment, where a conservative and a reactive tracer (3H and 51Cr(III)) were injected simultaneously and monitored in stream water and bed sediment. About 76% of the chromium was lost from the stream water on the reach 30 km downstream of the injection point directly after the passage of the pulse in the flowing water. The bed sediment hosted the main part of the retained chromium. The time to washout 75% of the maximum solute uptake in the sediment was ~85 times longer for chromium than for tritium (i.e. ~45 days). It was possible to describe the sediment-water exchange with a diffusive flux formulation that could be evaluated using tritium breakthrough curves in the stream water or the tritium inventory breakthrough curves in the sediment. This experiment revealed further that observations of chromium concentrations in the sediment were essential for the quantifying of sorption properties, as it was not possible to catch accurately the time scale of sorption within the duration of the breakthrough curves in the stream water. There was a clear need for a rate-limited description of the sorption of chromium in the sediment. We found that a first-order kinetic description of the sorption process could acceptably describe the breakthrough curves in both the stream water and the bed sediment.
Keywords: MODEL; SORPTION KINETICS; SEDIMENT; STREAM; TRACER EXPERIMENT; TRANSIENT STORAGE